The Increase in Students Activeness and Performance of Learning Geography Through Talking Stick Learning Method in Class X IIS 3 Sman 1 Pinggir - Jumiatri, Jumiatri; Khairani, Khairani (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
This research begins with a problem in the learning process that is not the expected learning process, as students are less active or have low student involvement in learning so that in the implementation of learning, the classroom atmosphere looks interesting. This research aims to obtain information, data and a picture of an increase in involvement in learning and know the learning outcomes of students of class X IIS 3 of SMA Negeri 1 Pinggir through the Talking Stick learning method. This research aims to obtain information, data, and an overview of increasing in learning involvement and knowing the learning outcomes of students of class X IIS 3 SMA Negeri 1 Pinggir through the Talking Stick learning method. This research is a class action research consisting of two cycles, in which each cycle consists of three meetings. Each meeting has four stages, namely planning, implementation, observation and reflection. The results show that through the talking stick learning method, it increases the activeness and learning outcomes of students of class X IIS 3 from the first cycle which is 67.7% and in the second cycle it increases to 85.2%.